Analisis Determinan Penghindaran Pajak Pada Perusahaan Industri Barang Konsumsi - Fajar Pratama Aji; Sartika Wulandari (Politeknik Ganesha Medan, 2022)
This research is a quantitative research that aims to analyze the factors that influence tax avoidance. The variables used include profitability, leverage, sales growth and earnings management. Source of data is obtained from the annual financial report on the Indonesian Stock Exchange (IDX). The population in this study are 98 consumer goods industrial sector companies listed on the IDX for the period 2016–2021 with purposive sampling method. Based on the purposive sampling method, 138 samples were obtained from 23 consumer goods industrial sector companies listed on the IDX for the period 2016–2021. The data analysis technique in this study used panel data using the Eviews 9 program. The results of this study show that profitability, leverage, sales growth and earning management have no effect on tax avoidance